Preface for J-PAND Supplement Issue: Project on Reducing the Risk of Nuclear Weapons Use in Northeast Asia (NU-NEA) - von Hippel, David F.; Hayes, Peter; Shetty, Shatabhisha; Suzuki, Tatsujiro; Yoshida, Fumihiko (Journal for peace and nuclear disarmament, 2022)
This supplement issue of Journal for Peace and Nuclear Disarmament presents the papers commissioned in 2021 to support the Project on Reducing the Risk of Nuclear Weapons Use in Northeast Asia (NU-NEA). The NU-NEA project was developed to study the risk contours and conflict terrain for war and nuclear escalation in and around the Korean peninsula. This study is being carried out in part by developing a set of plausible "use cases" for nuclear weapons in NEA, that is, cases in which a combination of nuclear weapons deployments, political, economic, or other circumstances in the region and/or internationally, and specific "triggering events" lead a state or non-state actor to detonate a nuclear weapon in the region ("first use"), followed by evolution of the nuclear conflict and its ultimate consequences. The commissioned papers that informed use case preparation were prepared by a group of authors from many nations and backgrounds, spanning topics from the history of the division of the ROK and DPRK to ROK military strategy, ballistic missile inventories and capabilities, counterforce issues, and many others. Nuclear use cases have been developed not to suggest probable outcomes, but to identify plausible outcomes so that policies can be devised and implemented to avoid any use of nuclear weapons, with the ultimate project goal being "let Nagasaki be the last".